Analisis Potensi Bahan Ajar Biologi Kelas XI Pada Kurikulum 2013 Dalam Memberdayakan Kemampuan Berkomunikasi Siswa - Anggit Sasmito; Suciati Suciati; Maridi Maridi (Scientiae Educatia: Jurnal Pendidikan Sains, 2017)
The purpose of this research was to analyze the biology materials of the eleventh grade on the material of the human excretion system on the potential of empowering students' communication skills in one of the Senior High School in Madiun Regency. The research uses the descriptive method. The Technique of collecting data with teaching material is observed potency of empowering its communication skill directly based on communication skill assessment instrument covering twelve indicators which are divided on the four aspects namely expression aspect, evaluation, response, and negotiation. The teaching materials that were analyzed included two biology books from two different publishers, especially the material of human excretion system in Basic Competence 3.9 and 4.9 from 2013 curriculum. Data analyzed uses descriptive quantitative analysis. The result of analysis shows that the potential of empowerment of communication skill in teaching materials is still low, it’s indicated by the low of indicator and the low percentage of indicator that emerged, from the twelve indicators only four indicators that emerged: the first indicator 27,3%, the third indicator 18,2%, the eighth indicator 27,3%, and the twelfth indicator 27,3%. Based on the results of the analysis can be concluded that the biology materials eleventh grade on the material excretion system used in one of the Senior High School in Madiun Regency has not the potential to empower students' communication skills.